Association Between PRRSV ORF5 Genetic Distance and Differences in Space, Time, Ownership and Animal Sources Among Commercial Pig Herds. Issue 2 (4th August 2014) - Rosendal, T.; Dewey, C.; Friendship, R.; Wootton, S.; Young, B.; Poljak, Z.
Summary: The objective of this study was to investigate associations between genetic distance of porcine reproductive and respiratory syndrome virus (PRRSV) detected in Ontario swine herds, and the distance between the herds with respect to space, time, ownership and animal sources. PRRSV sequence data between September 2004 and August 2007 were obtained from the Animal Health Laboratory of the University of Guelph. Geographical coordinates were obtained from the Ontario Pork marketing board, and network information about ownership and animal suppliers was obtained using a telephone interview. The matrices of sequence, spatial, temporal and network distances were generated and were analysed using the Mantel test, and using linear‐mixed models with P ‐values based on random permutations. A total of 438 PRRSV isolates from 329 premises and 232 ownerships were originally included; 57 of the isolates were considered vaccine type. The Mantel correlation test indicated that there was positive correlation between sequence distance and geographic distance ( r  = 0.11, P  = 0.001), as well as sequence distance and temporal distance ( r  = 0.03, P  = 0.03), with similar results reported after adjusting for the ownership distance. Mantel correlogram suggested existence of spatial correlation up to ~30 km distance. Multivariable linear‐mixed model for association between genetic distance and space–time distance was characterized by the three‐way interaction among space, time and ownership ( P  < 0.001). It suggested that positive association between sequence similarity and spatial proximity exists in herds under different ownerships, but its magnitude is very small. In contrast, for pairs of herds under identical ownership, the spatial association was more complex. This could be a consequence of interactions within ownerships, or alternatively decisions made about sampling of herds for diagnostic purposes. Of the networks evaluated, ownership ( P  < 0.001) and gilt supplier ( P  < 0.001) showed the highest magnitude of association with genetic distance and should be investigated further for their impact on disease spread.